2005
DOI: 10.1111/j.1365-2036.2005.02647.x
|View full text |Cite
|
Sign up to set email alerts
|

Capsule endoscopy – comparison of two strategies of bowel preparation

Abstract: SUMMARYBackground: Capsule endoscopy can identify lesions of the small bowel that cannot be detected by other techniques. In addition to patient safety, quality of care and cost-efficiency, good preparation is an important factor for good visualization. Aim: To evaluate the efficacy of oral sodium phosphate preparation. Methods: Forty-six consecutive patients scheduled for capsule endoscopy in two medical centres. The patients treated in Dallas were prepared by 12 h fasting (group A), and those treated in Isra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 27 publications
(24 reference statements)
2
37
0
4
Order By: Relevance
“…The results of the studies which investigated the effect of bowel preparation on CECR were not consistent with each other [15][16][17][18][19][20][21][22] , but improved image quality has been reported. Previous studies also investigated the role of endoscopic placement of capsule and/ or real-time viewing and showed that these approaches can improve CECR [23][24][25][26] .…”
Section: Discussionmentioning
confidence: 81%
“…The results of the studies which investigated the effect of bowel preparation on CECR were not consistent with each other [15][16][17][18][19][20][21][22] , but improved image quality has been reported. Previous studies also investigated the role of endoscopic placement of capsule and/ or real-time viewing and showed that these approaches can improve CECR [23][24][25][26] .…”
Section: Discussionmentioning
confidence: 81%
“…Preliminary results have already been published by our group [6]. Although similar studies exist (Table 6), none of the three abovementioned preparations have been compared in a randomized way, and have only been analysed in short series [5,7,8] or retrospectively [8]. A review of the related literature by Franchis et al [3] highlights the fact that studies published about this subject are scarce and provide inconsistent results.…”
Section: Discussionmentioning
confidence: 91%
“…No effect on the gastric or intestinal transit of the CE was detected, though a higher level of cleanliness was observed in the patients who had received PEG, among whom there was a statistically significant improvement of the diagnostic yield. Niv et al [8] published an analysis of the use of ASP in 46 versus 23 patients whose bowel preparation consisted solely of overnight fasting. The authors recommended preparation with ASP after observing a higher level of cleanliness.…”
Section: Discussionmentioning
confidence: 99%
“…Some abnormalities such as angiodysplasias are sometimes hampered by residual intestinal contents. Thus, a bowel preparation is studied previously, and sodium phosphate (Niv, 2005) or polyethylene glycol (PEG) (Viazis, 2004;Dai, 2005) has been described to offer improved visualization of the small intestine in adults.…”
Section: Preparations For Cementioning
confidence: 99%